Analyzing Deterioration in Ancient Documents through Preservation and Conservation Practices: A Systematic Literature Review - Syekhan Abdil Barr; Gilang Ramadhan; Khoilillah Fatikasari; Zulfatun Sofiyani (Anuva: Jurnal Kajian Budaya, Perpustakaan, dan Informasi, 2026)
This study analyzes deterioration in ancient documents and the preservation–conservation practices used to address it through a systematic literature review of 14 selected articles published between 2022 and 2025. Ancient documents remain highly vulnerable to complex deterioration mechanisms, including chemical degradation, ink corrosion, fungal activity, environmental instability, and mechanical fragility. Using the PRISMA framework, this review identifies recurring deterioration patterns, evaluates the effectiveness of preservation and conservation strategies, and highlights challenges in their implementation. Findings reveal that integrated approaches combining physical conservation, such as deacidification, fiber strengthening, fumigation, and antifungal treatments with digital methods, including high-resolution digitization, OCR, NLP, multispectral imaging, and AI-based restoration, provide the most effective protection. Scientific innovations, including nanocellulose and TiO₂-based treatments, show promising results in stabilizing aged documents, while digital preservation reduces physical handling and improves long-term accessibility. However, limitations remain, particularly in regions with restricted resources, where high equipment costs, limited expertise, and inconsistent conservation standards hinder optimal implementation. In the Indonesian context, tropical climatic conditions further increase the risk of biodeterioration and emphasize the need for scalable and sustainable preservation methods. This review concludes that future research must prioritize affordable conservation technologies, long-term evaluation of nanomaterials, enhancement of AI datasets for local scripts, and the integration of traditional, scientific, and digital approaches. These efforts are essential to ensure the long-term survival and accessibility of ancient documentary heritage.